The Japanese Banking Crisis - Himino, Ryozo (Springer Nature, 2021)
This open access book provides a readable narrative of the bubbles and the banking crisis Japan experienced during the two decades between the late 1980s and the early 2000s. Japan, which was a leading competitor in the world's manufacturing sector, tried to transform itself into an economy with domestic demand-led mature growth, but the ensuing bubbles and crisis instead made the country suffer from chronicle deflation and stagnation. The book analyses why the Japanese authorities could not avoid making choices that led to this outcome. The chapters are based on the lectures to regulators from emerging economies delivered at the Global Financial Partnership Center of the Financial Services Agency of Japan.